2023
DOI: 10.3390/ijms241713408
|View full text |Cite
|
Sign up to set email alerts
|

EGF, TGF-α and Amphiregulin Differently Regulate Endometrium-Derived Mesenchymal Stromal/Stem Cells

Rimma Sergeevna Kamentseva,
Marianna Viktorovna Kharchenko,
Gulnara Vladikovna Gabdrahmanova
et al.

Abstract: The prototypical receptor tyrosine kinase epidermal growth factor receptor (EGFR) is regulated by a set of its ligands, which determines the specificity of signaling and intracellular fate of the receptor. The EGFR signaling system is well characterized in immortalized cell lines such as HeLa derived from tumor tissues, but much less is known about EGFR function in untransformed multipotent stromal/stem cells (MSCs). We compared the effect of epidermal growth factor (EGF), transforming growth factor-α (TGF-α) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Ríos et al., in their study of bovine oocytes, found that the pro-maturation effect of EGF was evident in degranulated oocytes, indicating that EGF acts directly, or at least partially, on oocytes ( 33 ). A study on mice showed that the zona pellucida allows molecular substances, up to 150 kDa, to pass through ( 34 , 35 ). Therefore, we speculated that the human zona pellucida also has this characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Ríos et al., in their study of bovine oocytes, found that the pro-maturation effect of EGF was evident in degranulated oocytes, indicating that EGF acts directly, or at least partially, on oocytes ( 33 ). A study on mice showed that the zona pellucida allows molecular substances, up to 150 kDa, to pass through ( 34 , 35 ). Therefore, we speculated that the human zona pellucida also has this characteristic.…”
Section: Discussionmentioning
confidence: 99%